Splenic Sclerosing Angiomatoid Nodular Transformation in an 8-Year-Old Child - Ji Yeong Kim; Hee Jung Lee; Eun Young Jung; Hye Won Lee; Ye Jee Shim (Journal of the Korean Society of Radiology)
Sclerosing angiomatoid nodular transformation (SANT) of the spleen is extremely rare in pediatric patients. Here, we report the case of an 8-year-old boy with iron-deficiency anemia and a solitary splenic mass detected using US, CT, and MRI. The patient underwent partial splenectomy, and the final diagnosis was SANT. Herein, we discuss the radiological features of splenic SANT through a review of reported cases and the differential diagnosis of other primary splenic tumors.